A COMPREHENSIVE SYSTEMATIC REVIEW OF THE RELATIONSHIP BETWEEN EXERCISE-INDUCED ALLERGY AND FOOD-DEPENDENT EXERCISE-INDUCED ANAPHYLAXIS - Jeffy Marta (International Medical Journal Corp. Ltd, 2026)
Introduction: Exercise-induced anaphylaxis (EIA) and food-dependent exercise-induced anaphylaxis (FDEIA) represent physically triggered hypersensitivity disorders with contested nosological positioning. FDEIA has historically been classified as a physical allergy subtype, yet accumulating evidence suggests it constitutes a high-threshold, cofactor-dependent food allergy. This systematic review synthesized all primary interventional and observational evidence describing the epidemiological, immunological, diagnostic, mechanistic, and prognostic relationship between these entities. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligibility was restricted a priori to randomized controlled trials, interventional/provocation studies, cohort, case-control, cross-sectional, and epidemiological survey designs. Two reviewers independently screened, extracted, and appraised records using a dual risk-of-bias architecture (modified Newcastle-Ottawa/JBI composite and RoB 2/ROBINS-I), with GRADE certainty grading across fifteen prespecified outcome domains. Results: Fifty primary studies (up to 2026), encompassing >6,900 patients and >600,000 surveyed children, met eligibility. Population prevalence rose from 0.0047% in elementary to 0.017–0.018% in junior-high students, with male predominance in adolescence. Wheat was the dominant culprit globally; non-specific lipid transfer proteins (nsLTP) predominated in Mediterranean populations (66.3–78%). Component-resolved serology achieved 80–91% sensitivity and 92% specificity for omega-5 gliadin, rising to 93.8% sensitivity/92.9% specificity with recombinant high-molecular-weight glutenin. Exercise lowered median eliciting gluten dose from 48g to 24g (−63%) and increased severity from 1.1 to 2.3; aspirin reduced threshold by 83%, exercise-plus-aspirin by 87%. Structured avoidance prevented further anaphylaxis in 91.7% (elimination) and 87.0% (temporal separation), yet 20–33% continued to react. Diagnostic delay ranged from 16 months to >5 years. Overall GRADE certainty was moderate for diagnostic-accuracy and cofactor-threshold domains, low-to-very-low for prevalence, treatment, and prognostic domains. Discussion: FDEIA is reconceptualized as a cofactor-dependent, high-threshold IgE-mediated food allergy rather than a physical allergy, positioning EIA and FDEIA on a single mechanistic continuum modulated by allergen dose, cofactor load, and epithelial permeability. Two molecular archetypes dominate: gliadin/glutenin in East Asia and Northern Europe, nsLTP in the Mediterranean. Cofactor hierarchy (exercise+aspirin > aspirin > exercise > alcohol) provides the first quantitative framework for clinical risk counseling. Persistent limitations include absence of randomized evidence, heterogeneous protocols, and geographical under-representation. Conclusion: Exercise-induced allergy and FDEIA are mechanistically inseparable expressions of a shared cofactor-dependent hypersensitivity continuum. Component-resolved diagnostics, cofactor-augmented titrated challenge, and structured allergen-exercise temporal separation constitute current evidence-based standards, but residual breakthrough risk mandates universal adrenaline auto-injector provision. Priority research includes randomized cofactor-controlled protocols, validated pediatric molecular panels, prospective registries in under-represented regions, and biologic/immunotherapeutic trials.